The expanding capability and clinical relevance of molecular diagnostic technology to identify and evaluate EGFR mutations in advanced/metastatic NSCLC. (October 2021) - Shah, Parth; Sands, Jacob; Normanno, Nicola
Highlights: EGFR mutation testing is critical to select therapies for advanced NSCLC. Over recent years there has been a rapid development in testing methodologies. Use of mutation testing has therefore expanded throughout the disease course. There are also expanded panels of genetic mutations for testing of NSCLC patients. We review current mutation testing in the clinic and likely future developments. The expanding capability and clinical relevance of molecular diagnostic technology to identify and evaluate EGFR mutations in advanced/metastatic NSCLC. Abstract: Epidermal growth factor receptor ( EGFR ) mutation testing in advanced non-small-cell lung cancer (NSCLC) has evolved rapidly over the past decade, largely triggered by the introduction of the targeted EGFR tyrosine kinase inhibitors (TKIs). Initially used to detect common EGFR mutations and determine the most appropriate first-line therapy at diagnosis, testing methodologies have expanded to test for multiple mutations at multiple time points throughout the disease course. Here we review the current mutation testing approaches, including types of biopsies, and the available assays commonly used in the clinic. Specific application of these approaches in advanced NSCLC, including current guideline recommendations, and potential future developments are discussed.